Pola Sebaran Permukiman Kumuh di Kabupaten Tangerang dan Keragaman Spasial Faktor yang Mempengaruhinya: Distribution Pattern of Slums in Tangerang Regency and Spatial Diversity Factors that Affect - Muchamad Subhans Adiputra; Ernan Rustiadi; Andrea Emma Pravitasari (P4W LPPM IPB, 2022)
Rapid development and high population density are among the factors that cause slum settlements Tangerang Regency. Factors that cause slum settlements in Tangerang Regency have not been identified specifically and the handling of slum settlements are still seen to be uniform between regions. The purpose of this research is to identify the pattern of distribution of slum settlements in Tangerang Regency and the spatial diversity of factors that influence it. Methods used to identify the distribution pattern of slums are Moran's Index, Moran's Scatterplot, and Local Indicator Spatial Autocorrelation. Meanwhile, to understand the spatial diversity of the factors that affect slum settlements, multiple regression analysis was performed using forward stepwise regression, followed by Geographically Weighted Regression (GWR) analysis. Results shows that the pattern of spatial distribution of slum settlements in 2016 and 2018 was concentrated in the northern and southern areas of Tangerang Regency. The distribution pattern of slums shows a centered movement towards the district border with the surrounding areas, namely DKI Jakarta, Tangerang City, and South Tangerang City. The relationship between the Village Development Index and the Land Value Zone has a fairly weak positive correlation, the relationship between the Kelurahan Development Index and the percentage of slum area does not have a significant correlation, while the Land Value Zone with the percentage of slum area has a weak positive correlation. Slum settlements in Tangerang Regency are influenced by physical and non-physical factors including the number of slum location points, the percentage of residential buildings that do not have a building permit, and the percentage of areas affected by inundation. The results of the GWR analysis show that each factor that has a significant influence on slum settlements in Tangerang Regency has a different influence locally in each observed area.